Prevention and Treatment of Chemotherapy-Induced Alopecia - Alfredo Rossi; Gemma Caro; Maria Caterina Fortuna; Flavia Pigliacelli; Andrea D'Arino; Marta Carlesimo (Mattioli1885, 2020)
Background: Chemotherapy-induced alopecia (CIA) is one of the most dramatic side effects of chemotherapy. Currently no guidelines are available for its prevention and treatment. Several devices and drugs are used, but results are often disappointing. Aims: Our aim is to analyze drugs and devices proposed in the literature for prevention and treatment of CIA induced by cytotoxic drugs and to discuss the evidenced-based opinion. Methods and Results: Scalp cooling is the only agent that has been approved by the US Food and Drug Administration for CIA prevention. Minoxidil and bimatoprost should not be used during chemotherapy administration, but they can be used after chemotherapy discontinuation to obtain greater regrowth. Conclusions: Therapy should always be modulated for the patient and no fixed protocol should be used. Trichoscopy and trichogram could be useful tools in supporting this treatment.